Genetic diversity and recombination analysis of sweepoviruses from Brazil - Albuquerque Leonardo C; Inoue-Nagata Alice K; Pinheiro Bruna; Resende Renato O; Moriones Enrique; Navas-Castillo Jesús (Virology Journal, 2012)
Abstract Background Monopartite begomoviruses (genus Begomovirus, family Geminiviridae) that infect sweet potato (Ipomoea batatas) around the world are known as sweepoviruses. Because sweet potato plants are vegetatively propagated, the accumulation of viruses can become a major constraint for root production. Mixed infections of sweepovirus species and strains can lead to recombination, which may contribute to the generation of new recombinant sweepoviruses. Results This study reports the full genome sequence of 34 sweepoviruses sampled from a sweet potato germplasm bank and commercial fields in Brazil. These sequences were compared with others from public nucleotide sequence databases to provide a comprehensive overview of the genetic diversity and patterns of genetic exchange in sweepoviruses isolated from Brazil, as well as to review the classification and nomenclature of sweepoviruses in accordance with the current guidelines proposed by the Geminiviridae Study Group of the International Committee on Taxonomy of Viruses (ICTV). Co-infections and extensive recombination events were identified in Brazilian sweepoviruses. Analysis of the recombination breakpoints detected within the sweepovirus dataset revealed that most recombination events occurred in the intergenic region (IR) and in the middle of the C1 open reading frame (ORF). Conclusions The genetic diversity of sweepoviruses was considerably greater than previously described in Brazil. Moreover, recombination analysis revealed that a genomic exchange is responsible for the emergence of sweepovirus species and strains and provided valuable new information for understanding the diversity and evolution of sweepoviruses.